Struktura fizyczna gruntu, zawartość substancji organicznej oraz skład chemiczny gleb w podłożach 21 stanowisk zieleni miejskiej na terenie Poznania. Część III. Zawartość makroelementów: N, P, K, S, Ca i Mg - Łukasiewicz, Szymon (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
This article is a continuation of a four-piece work describing the condition of soil in what has been broadly defined as central Poznań. This article presents the content of active forms of six chemical elements which tend to be absorbed by plants in biggest quantities. Relations between these chemical elements are discussed and indications are made of how to counteract the negative effects of deficits as well as overdoses of specific chemical elements in the substrate.
Keywords: soil macroelements; anthropogenic soils; city ecology; horse-chestnut; Aesculus hippocastanum L.